answersLogoWhite

0


Best Answer

Simplifying

4x + -5 = 2x + 7

Reorder the terms:

-5 + 4x = 2x + 7

Solving

-5 + 4x = 7 + 2x

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.

-5 + 4x + -2x = 7 + 2x + -2x

Combine like terms: 4x + -2x = 2x

-5 + 2x = 7 + 2x + -2x

Combine like terms: 2x + -2x = 0

-5 + 2x = 7 + 0

-5 + 2x = 7

Add '5' to each side of the equation.

-5 + 5 + 2x = 7 + 5

Combine like terms: -5 + 5 = 0

0 + 2x = 7 + 5

2x = 7 + 5

Combine like terms: 7 + 5 = 12

2x = 12

Divide each side by '2'.

x = 6 (your answer)

User Avatar

Imgenplyz

Lvl 3
โˆ™ 2020-12-01 20:50:18
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.8
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1499 Reviews

Add your answer:

Earn +20 pts
Q: What is (4x-5)and(2x+7) in simplest form?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked